AVALIAÇÃO DA UTILIZAÇÃO ÁCIDOS ORGÂNICOS SOBRE A QUALIDADE DA CAMA DE AVIÁRIO - Aniecevski, Edemar; Petrolli, Tiago Goulart (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
In poultry farming, the production environment favors the multiplication of pathogens or other undesirable bacteria, and among these organisms are, mainly, bacteria of the genus Salmonella, resulting in problems inherent to food safety, causing carcass condemnation and other serious related problems public health. The objective of this study was to evaluate the effect of adding a blend of organic acids, their salts and lignin derivatives for the treatment of poultry litter, verifying their influence on the count of enterobacteria (CFU/g), pH behavior, water activity (Aw) and the moisture content in the litter. The research was conducted in three commercial aviaries, with an area of ​​480m2 each, with the same date of housing for the birds. The product was added to the aviary litter, in dosages of 40, 80 and 120g/m², 48 hours before the housing of the birds, throughout the entire length of the aviary. The collection of samples for analysis (microbiological, pH, water activity and humidity) was carried out at eight points in each shed at different time periods. To evaluate the total bacterial count of aerobic mesophiles, the deep plating technique was used, the pH was measured using a digital pHmeter, the water activity was performed using the LabSwift-aw equipment and the litter moisture analysis were performed according to the techniques described by Silva and Queiroz (2009). The total microbial count was reduced by more than 50% through the addition of the product on the bed of the aviaries, with a reduction in the count in the samples collected six hours after applying the blend, at a dosage of 120 grams/m². In the litter analysis at 14 days of lot creation, it was observed that the microbial count in litter treated with the different blend doses returned to initial levels. After 28 days, the addition of the blend, in all tested dosages, was not enough to promote a delay in microbial growth. This behavior may be associated with acid volatility. The parameters of pH, water activity and moisture were not influenced by the additives applied to the litter. It is concluded that the acids added on the poultry litter, during the interval between batches, have a mitigating effect on microbial proliferation up to 14 days of age. They have no effect on pH, water activity and moisture content in poultry litter.